Different Cognitive Frailty Models and Health- and Cognitive-related Outcomes in Older Age: From Epidemiology to Prevention. - Panza, Francesco; Lozupone, Madia; Solfrizzi, Vincenzo; Sardone, Rodolfo; Dibello, Vittorio; Di Lena, Luca; D'Urso, Francesca; Stallone, Roberta; Petruzzi, Massimo; Giannelli, Gianluigi; Quaranta, Nicola; Bellomo, Antonello; et al. (J Alzheimers Dis, 2018)
Frailty, a critical intermediate status of the aging process that is at increased risk for negative health-related events, includes physical, cognitive, and psychosocial domains or phenotypes. Cognitive frailty is a condition recently defined by operationalized criteria describing coexisting physical frailty and mild cognitive impairment (MCI), with two proposed subtypes: potentially reversible cognitive frailty (physical frailty/MCI) and reversible cognitive frailty (physical frailty/pre-MCI subjective cognitive decline). In the present article, we reviewed the framework for the definition, different models, and the current epidemiology of cognitive frailty, also describing neurobiological mechanisms, and exploring the possible prevention of the cognitive frailty progression. Several studies suggested a relevant heterogeneity with prevalence estimates ranging 1.0-22.0% (10.7-22.0% in clinical-based settings and 1.0-4.4% in population-based settings). Cross-sectional and longitudinal population-based studies showed that different cognitive frailty models may be associated with increased risk of functional disability, worsened quality of life, hospitalization, mortality, incidence of dementia, vascular dementia, and neurocognitive disorders. The operationalization of clinical constructs based on cognitive impairment related to physical causes (physical frailty, motor function decline, or other physical factors) appears to be interesting for dementia secondary prevention given the increased risk for progression to dementia of these clinical entities. Multidomain interventions have the potential to be effective in preventing cognitive frailty. In the near future, we need to establish more reliable clinical and research criteria, using different operational definitions for frailty and cognitive impairment, and useful clinical, biological, and imaging markers to implement intervention programs targeted to improve frailty, so preventing also late-life cognitive disorders.

Nutritional Intervention as a Preventive Approach for Cognitive-Related Outcomes in Cognitively Healthy Older Adults: A Systematic Review. - Solfrizzi, Vincenzo; Agosti, Pasquale; Lozupone, Madia; Custodero, Carlo; Schilardi, Andrea; Valiani, Vincenzo; Sardone, Rodolfo; Dibello, Vittorio; Di Lena, Luca; Lamanna, Angela; Stallone, Roberta; Bellomo, Antonello; et al. (J Alzheimers Dis, 2018)
The link diet-cognitive function/dementia has been largely investigated in observational studies; however, there was a lack of evidence from randomized clinical trials (RCTs) on the prevention of late-life cognitive disorders though dietary intervention in cognitively healthy older adults. In the present article, we systematically reviewed RCTs published in the last four years (2014-2017) exploring nutritional intervention efficacy in preventing the onset of late-life cognitive disorders and dementia in cognitively healthy subjects aged 60 years and older using different levels of investigation (i.e., dietary pattern changes/medical food/nutraceutical supplementation/multidomain approach and dietary macro- and micronutrient approaches) as well as possible underlying mechanisms of nutritional prevention. From the 35 included RCTs, there was moderate evidence that intervention through dietary pattern changes, medical food/nutraceutical supplementation, and multidomain approach improved specific cognitive domains or cognitive-related blood biomarkers. There was high evidence that protein supplementation improved specific cognitive domains or functional status in prefrail older adults without effect.

Social Dysfunction in Older Age and Relationships with Cognition, Depression, and Apathy: The GreatAGE Study. - Lozupone, Madia; Panza, Francesco; Piccininni, Marco; Copetti, Massimiliano; Sardone, Rodolfo; Imbimbo, Bruno P; Stella, Eleonora; D'Urso, Francesca; Barulli, Maria Rosaria; Battista, Petronilla; Grasso, Alessandra; Tortelli, Rosanna; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Most studies focused on only one measure of social dysfunction in older age, without proper validation and distinction across different dimensions including subjectivity, structural, and functional aspects. OBJECTIVE: We sought to validate the Social Dysfunction Rating Scale (SDRS) and its factorial structure, also determining the association of SDRS with cognitive functions, global psychopathology, and social deprivation. METHODS: The SDRS was administered to 484 Italian community-dwelling elderly, recruited in the GreatAGE study, a population-based study on aging conducted in Castellana Grotte, Bari, Southern Italy. We determined objective and subjective psychometric properties of SDRS against the gold standard evaluation of social dysfunction according to the Semi-structured Clinical Diagnostic Interview for DSM-IV-TR Axis I Disorders (SCID-I) criterion. RESULTS: The SDRS showed a moderate accuracy with an optimal cut-off of 26 maximized with higher sensitivity (0.74,95% CI:0.63-0.84) than specificity (0.57,95% CI:0.50-0.64). A five-factor structure was carried out and five dimensions of SDRS were identified (loneliness; social isolation; feeling of contribution/uselessness; lack of leisure activities; anxiety for the health). Education and global cognitive functions were inversely correlated to SDRS, while a direct association with global psychopathology, depression, and apathy was found. The prevalence of higher SDRS scores was major in subjects with current psychiatric disorders versus other subjects.∥Conclusion: The SDRS could be a valid instrument to capture both size and quality of social dysfunction, both in subjects with psychiatric disorders and in normal subjects. Several categories of social dysfunction differed only in the degree of health deprivation, not in social or material deprivation.

Relationships of Dietary Patterns, Foods, and Micro- and Macronutrients with Alzheimer's Disease and Late-Life Cognitive Disorders: A Systematic Review. - Solfrizzi, Vincenzo; Custodero, Carlo; Lozupone, Madia; Imbimbo, Bruno P; Valiani, Vincenzo; Agosti, Pasquale; Schilardi, Andrea; D'Introno, Alessia; La Montagna, Maddalena; Calvani, Mariapaola; Guerra, Vito; Sardone, Rodolfo; et al. (J Alzheimers Dis, 2017)
In the last decade, the association between diet and cognitive function or dementia has been largely investigated. In the present article, we systematically reviewed observational studies published in the last three years (2014-2016) on the relationship among dietary factors and late-life cognitive disorders at different levels of investigation (i.e., dietary patterns, foods and food-groups, and dietary micro- and macronutrients), and possible underlying mechanisms of the proposed associations. From the reviewed evidence, the National Institute on Aging-Alzheimer's Association guidelines for Alzheimer's disease (AD) and cognitive decline due to AD pathology introduced some evidence suggesting a direct relation between diet and changes in the brain structure and activity. There was also accumulating evidence that combinations of foods and nutrients into certain patterns may act synergistically to provide stronger health effects than those conferred by their individual dietary components. In particular, higher adherence to a Mediterranean-type diet was associated with decreased cognitive decline. Moreover, also other emerging healthy dietary patterns such as the Dietary Approach to Stop Hypertension (DASH) and the Mediterranean-DASH diet Intervention for Neurodegenerative Delay (MIND) diets were associated with slower rates of cognitive decline and significant reduction of AD rate. Furthermore, some foods or food groups traditionally considered harmful such as eggs and red meat have been partially rehabilitated, while there is still a negative correlation of cognitive functions with saturated fatty acids and a protective effect against cognitive decline of elevated fish consumption, high intake of monounsaturated fatty acids and polyunsaturated fatty acids (PUFA), particularly n-3 PUFA.